การประเมินเครื่องมือตรวจคัดกรองความเสี่ยงการเกิดโรคฟันผุในเด็กปฐมวัย 3 ชนิด ในเด็กอายุ 1-3 ปี - ชัชฎาภรณ์ ปลอดโปร่ง (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Objective: To evaluate the clinical ability of a caries risk assessment tools for identifying association of ECC with plaque levels, saliva streptococcus mutans (S. mutans) levels, saliva pH and buffering capacity (BC) in 1-3 years old children. Materials and methods: This study consisted of 100 children. The children were examined and recorded the ECC status. The level of plaque was scored using bevel edged straw scrubbing. The level of S. mutans and the properties of unstimulted saliva were determined by Saliva-Check MUTANS® and Saliva-Check BUFFER®, respectively. Results: The prevalence of ECC is 59%. Plaque and saliva S. mutans levels were associated with ECC whereas saliva pH and BC were not. The odd for high plaque and high S. mutans level groups were 7.9 and 2.8 times respectively greater to develop ECC than low group. In ECC group, the high plaque children were more dmft and dmfs scored than the low plaque children. As the same for S. mutans level whereas saliva pH and BC, dmft and dmts scored between each subgroup were not different. Conclusion: Plaque and saliva S. mutans levels were associated with ECC whereas saliva pH and BC were not